Residual pulmonary hypertension after pulmonary endarterectomy: A meta-analysis - Hsieh, Wan Chin; Jansa, Pavel; Huang, Wei Chun; Nižnanský, Matus; Omara, Mohamend; Lindner, Jaroslav (The Journal of thoracic and cardiovascular surgery, 2018)
OBJECTIVE: Chronic thromboembolic pulmonary hypertension is surgically treated through pulmonary endarterectomy. Although pulmonary endarterectomy is the treatment of choice for chronic thromboembolic pulmonary hypertension in terms of both functional outcomes and survival, many patients experience persistent pulmonary hypertension after pulmonary endarterectomy. The study objective was to calculate the pooled estimates of outcomes after pulmonary endarterectomy, including persistent pulmonary hypertension. METHODS: Meta-analyses were conducted on published studies reporting residual/persistent/recurrent pulmonary hypertension in 4868 patients with chronic thromboembolic pulmonary hypertension after pulmonary endarterectomy. The rate of persistent pulmonary hypertension and change in mean pulmonary artery pressure, pulmonary vascular resistance, and 6-minute walk distance after pulmonary endarterectomy were outcomes of interest. RESULTS: Twenty-five percent of patients with chronic thromboembolic pulmonary hypertension were diagnosed with persistent pulmonary hypertension after pulmonary endarterectomy. Pulmonary endarterectomy reduced mean pulmonary artery pressure and pulmonary vascular resistance by approximately 21 mm Hg (standardized mean difference, 1.75; 95% confidence interval, -1.62 to 1.88; P < .00001) and 561 dyn.s/cm5 (standardized mean difference, 1.64; 95% confidence interval, -1.58 to 1.70; P < .00001), respectively. Conversely, 6-minute walk distance increased by 96 m (standardized mean difference, -0.83; 95% confidence interval, -0.91 to -0.76; P < .00001) after pulmonary endarterectomy. CONCLUSIONS: Pulmonary endarterectomy is the gold standard treatment for chronic thromboembolic pulmonary hypertension and provides immediate correction of hemodynamic parameters in most patients. However, in up to one quarter of operable cases, pulmonary hypertension persists after surgery. In those patients with persistent pulmonary hypertension, continued medical management with newer agents may be required to improve pulmonary hemodynamics and, therefore, patient outcomes.
Keywords: Humans; lidé středního věku; plicní tlak v zaklínění; Female; rizikové faktory; dospělí; výsledek terapie; lidé; Hypertension, Pulmonary; plicní embolie; Pulmonary Embolism; mean pulmonary artery pressure; Adult; plicní hypertenze; ženské pohlaví; Male; Middle Aged; pulmonary thromboendarterectomy; Treatment Outcome; Endarterectomy; endarterektomie; pulmonary vascular resistance; mužské pohlaví; Pulmonary Wedge Pressure; pulmonary endarterectomy; chronic thromboembolic pulmonary hypertension; Risk Factors